Does night-time public transport contribute to inclusive night mobility? Exploring Sofia's night bus network from a gender perspective. (March 2020) - Plyushteva, Anna; Boussauw, Kobe
Highlights: Examines the implications of a new night bus service for gender-inclusive mobility. Argues research on gender and night mobility should not focus exclusively on safety. Alongside safety, adds dimensions of cost, distances and destinations, and immobility.